2019
DOI: 10.1093/nar/gkz347
|View full text |Cite
|
Sign up to set email alerts
|

modEnrichr: a suite of gene set enrichment analysis tools for model organisms

Abstract: High-throughput experiments produce increasingly large datasets that are difficult to analyze and integrate. While most data integration approaches focus on aligning metadata, data integration can be achieved by abstracting experimental results into gene sets. Such gene sets can be made available for reuse through gene set enrichment analysis tools such as Enrichr. Enrichr currently only supports gene sets compiled from human and mouse, limiting accessibility for investigators that study other model organisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 48 publications
1
72
0
Order By: Relevance
“…Not only did we find that HCDs were associated with more highly expressed genes than super-enhancers, but we also found that they were associated with genes that are better able to identify erythroid cell types in the Mouse Gene Atlas than genes associated with superenhancers, using Enrichr cell type analysis software 18,19 (Figure 2B, Supplementary File 2).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Not only did we find that HCDs were associated with more highly expressed genes than super-enhancers, but we also found that they were associated with genes that are better able to identify erythroid cell types in the Mouse Gene Atlas than genes associated with superenhancers, using Enrichr cell type analysis software 18,19 (Figure 2B, Supplementary File 2).…”
Section: Resultsmentioning
confidence: 78%
“…Microarray expression data for e14.5 fetal liver (maturational stages proerythroblast, basophilic erythroblast, and polychromatic erythroblast) available through ErythronDB (http://www.cbil.upenn.edu/ErythronDB/resources.jsp) were downloaded and used to associate nearby gene expression to domains and non-domains 16,17 . Enrichr (http://amp.pharm.mssm.edu/Enrichr/) was used to perform comprehensive enrichment analysis on associated genes 18,19 .…”
Section: Hcd Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Genes related to diseases, geneto-protein interactions, and protein-protein interaction information can be found in the GenBank 12.21 and String Databases 11.0. We searched signalling pathways related to biomolecules in the Enrichr [11] and Kyoto Encyclopedia of Genes and Genomes (KEGG) . Cytoscape 3.7.1 and systemsdock 4.2.6 were used for network construction and molecular docking respectively.…”
Section: Methodsmentioning
confidence: 99%